Neuroleptic malignant syndrome in a patient on long-term olanzapine treatment at a stable dose: Successful treatment with dantrolene. (May 2015) - Kouparanis, Antonios; Bozikas, Andreas; Spilioti, Martha; Tziomalos, Konstantinos
Abstract Background: Neuroleptic malignant syndrome (NMS) is a rare life-threatening disorder resulting from treatment with neuroleptic agents and other drugs that act as dopamine antagonists. NMS most often occurs shortly after the initiation, dose increase or withdrawal of the offending agent, but can rarely occur after long-term treatment at stable doses. Immediate discontinuation of the causative agent (or re-administration if the cause is the withdrawal of neuroleptic therapy) along with supportive therapy to maintain cardiorespiratory stability and to reduce fever are the cornerstone of the management of NMS. Additional 'specific' treatments include dantrolene, bromocriptine and amantadine, but their role in the management of NMS is controversial. Case study: This study reports the case of NMS associated with long-term treatment with olanzapine at a stable dose. Administration of dantrolene was well-tolerated and resulted in prompt resolution of NMS symptoms.